Diagnostic and Prognostic Biomarkers for Myocardial Infarction - Wu, Yuling; Pan, Nana; An, Yi; Xu, Mengyuan; Tan, Lijuan; Zhang, Lijuan (Frontiers in Cardiovascular Medicine, 2021)
The incidence of myocardial infarction (MI) increases every year world widely. Better diagnostic and prognostic biomarkers for clinical applications are the consistent pursuit of MI research field. In addition to electrocardiogram, echocardiography, coronary angiography, etc., circulating biomarkers are essential for the diagnosis, prognosis and treatment effect monitoring of MI patients. In this review, we assessed both strength and weakness of MI circulating biomarkers including those: 1. originated from damaged myocardial tissues including current golden standard cardiac troponin, 2. released from non-myocardial tissues due to MI-induced systems reactions, and 3. preexisted in blood circulation before the occurrence of MI event. We also summarized newly reported MI biomarkers. We proposed that the biomarkers preexisted in blood circulation before MI incidents should be emphasized in research and development for MI prevention in near future.